Advanced introduction to private international law and procedure - Hay, Peter, 1935- (Cheltenham, UK ; Northampton, MA, USA : Edward Elgar Publishing, 2018)
"Litigating disputes in international civil and commercial cases presents a number of special challenges. Which country's courts have jurisdiction, and where is it advantageous to sue? Given the international elements of the case, which country's law will the court apply? Finally, if a successful plaintiff cannot find enough local assets, what does it take to have the judgment recognized and enforced in a country with assets? [This book] addresses these questions in a concise overview of the field. Key features include: comparative overview of legal systems, contrasting Anglo-American common law and the civil law approach of the European Union; addresses classic choice of law as well as international civil procedure; problem-oriented presentation; three parts presenting principal problems parties face in dealing with cases with an international dimension; and considers how the field could develop in the future."--
Preface -- Introduction: Basic issues -- Forum-selection clauses -- Jurisdiction over persons and things -- What law applies? -- Recognition and enforcement of foreign judgments -- An assessment : tasks, developments, trends.
Includes bibliographical references (pages [139]-141) and index.
Keywords: Conflict of laws; Conflict of laws -- Civil procedure; Procedure (Law); Conflict of laws; Procedure (Law)